2010
DOI: 10.1186/1471-2229-10-216
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of molecular and phenotypic diversity in pearl millet [Pennisetum glaucum (L.) R. Br.] from West and Central Africa and their relation to geographical and environmental parameters

Abstract: BackgroundThe distribution area of pearl millet in West and Central Africa (WCA) harbours a wide range of climatic and environmental conditions as well as diverse farmer preferences and pearl millet utilization habits which have the potential to lead to local adaptation and thereby to population structure. The objectives of our research were to (i) assess the geographical distribution of genetic diversity in pearl millet inbreds derived from landraces, (ii) assess the population structure of pearl millet from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 36 publications
(44 reference statements)
9
58
7
Order By: Relevance
“…The SSR molecular markers are known to be efficient for genetic diversity studies of pearl millet (Mariac et al, 2006;Bashir et al, 2015;Shakhatreh et al, 2015). The current study showed a lower average (4.071) number of alleles per locus compared to that reported by Mariac et al (2006) which was 6.2 for 421 cultivated accessions from Niger, and 16.4 for accessions from a wide geographic range in West and Central Africa (Stich et al, 2010). Other authors reported the analysis of 214 Sudanese pearl millet accessions in which they found a high level of alleles was reported with an average of 13.3 per locus (Bashir et al, 2015).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“…The SSR molecular markers are known to be efficient for genetic diversity studies of pearl millet (Mariac et al, 2006;Bashir et al, 2015;Shakhatreh et al, 2015). The current study showed a lower average (4.071) number of alleles per locus compared to that reported by Mariac et al (2006) which was 6.2 for 421 cultivated accessions from Niger, and 16.4 for accessions from a wide geographic range in West and Central Africa (Stich et al, 2010). Other authors reported the analysis of 214 Sudanese pearl millet accessions in which they found a high level of alleles was reported with an average of 13.3 per locus (Bashir et al, 2015).…”
Section: Discussioncontrasting
confidence: 52%
“…Overall, 22 Beninese pearl millet accessions have been sampled as part of larger studies targeting landraces spanning Western and Central Africa (Haussmann et al, 2006;Stich et al, 2010), and stored in the international genebank. However, these population is insufficient to provide information of their genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The two polymorphic primers were used for cluster analysis. In previous studies, Stich et al (2010) observed more number of alleles per locus, while analyzing diversity in germplasm lines. Similarly, Kapila et al (2008) found an average of 6.26 alleles per locus, in a set of maintainer lines.…”
Section: Molecular Marker Analysismentioning
confidence: 99%